A step-by-step guide to performing cancer metabolism research using custom-made media - Seifert, Sophie; Yanqui-Rivera, Francisco; Kühn, Tim; Høyland, Lena Elise; Borteçen, Toman; Agranovich, Bella; Eckhardt, Lara Elea; Herdt, Martin; Henneberg, Alessa L.; Panitz, Verena; Hayat, Faisal; Migaud, Marie; et al. (Life science alliance, 2026)
The preparation of custom-made media offers precise control over nutrient composition, enabling detailed studies of cellular metabolism. We demonstrate how self-made media formulations enable diverse assay designs and readouts to assess cancer metabolism. Self-made media can be used in Seahorse assays to measure mitochondrial respiration under defined conditions. In nutrient deprivation experiments, amino acid or vitamin removal can uncover how cancer cells adapt to metabolic stress. Using labeled amino acids enables analysis of nascent protein synthesis and translational regulation, while stable-isotope tracing reveals metabolic fluxes through key pathways. This guide presents a suite of metabolic assays using custom-made media, covering experimental design, the selection of controls, sample preparation, data acquisition, and interpretation. The accompanying online media calculator “Media Minds” streamlines the creation of custom media formulations, ensuring accuracy and reproducibility.
Online veröffentlicht: 10. Dezember 2025
Gesehen am 02.03.2026